MATHEMATICAL MODELS OF MULTIDIMENSIONAL DATA - V. S. Mukha (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The review of modern state of the problem of the multidimensional data analysis is given. The new mathematical models of the multidimensional data are considered.